After roads and dams: what role for engineers in the poverty reduction strategies of bilateral development agencies? - Harpham, Trudy; Anelay, Lance (Journal of international development, 1999)
The role of engineers within the major bilateral development agencies is currently subject to change as agencies' foci converge on poverty reduction, expressed in their support for the Organization for Economic Co‐operation and Development's (OECD) agreed aim of reducing by half the proportion of people living in extreme poverty by 2015. The focus of development aid has shifted from the prioritization of macroeconomic growth, allied to a flawed assumption that this would filter down to the poor, to a focus on pro‐poor growth that provides the poor with the necessary access to the economy and to services that meet their basic needs. Engineers perceive a risk of being marginalized within this new agenda. In many cases their reputations have been closely linked with the construction of large infrastructure projects designed to stimulate macroeconomic growth, the benefits of which were not perceived to have directly benefited the poor. This case study of a bilateral agency found that engineers have a clear role within the new agenda, and moreover that engineers were, in many cases, unfairly maligned for their previous work. Much of their problem appears to have been one of image resulting from a failure to effectively demonstrate results. This is an issue being tackled by many bilaterals across their sectors: improved needs assessments, indicators and evaluations being among their aims. To achieve this, development practitioners, including engineers will need to improve their use of participatory techniques, involving the poor in the planning, implementation and management of projects/programmes. The paper recommends methods that development practitioners, including engineers, should use to improve the impact of their interventions. These include the use of participatory methodologies to foster project/programme ownership by beneficiaries, contributing to the selection of appropriate donor inputs and long‐term sustainability. The paper supports a move being made by many of the bilaterals away from a project to a broader programme approach to development, within which sectors and disciplines work together to deliver a useful mix of poverty reducing measures. Copyright © 1999 John Wiley & Sons, Ltd.